Comparison of all-cause mortality with different blood glucose control strategies in patients with diabetes in the ICU: a network meta-analysis of randomized controlled trials - Xi Li; Jiahao Meng; Xingui Dai; Pan Liu; Yumei Wu; Shuhao Wang; Heng Yin; Shuguang Gao (Annals of Intensive Care)
Abstract Background The optimal glucose control strategy for intensive care unit (ICU) patients with diabetes remains a topic of debate. This study aimed to compare the effects of strict glucose control, intermediate strict glucose control, liberal glucose control, and very liberal glucose control on reducing all-cause mortality in ICU patients with diabetes through a network meta-analysis. Methods We conducted a search in PubMed, Cochrane Library, Embase, and Web of Science for randomized controlled trials comparing different glucose control strategies in ICU patients with diabetes up to October 1, 2024. The primary outcome was all-cause 90-day mortality. The Risk of Bias 2 tool was used to assess bias in the included studies. Data analysis was performed using Stata (version 17). Results A total of 12 randomized controlled trials involving 5,297 participants were included in the final analysis. The results showed that there was no statistically significant difference between the four glucose control strategies in reducing all-cause 90-day mortality. The surface under the cumulative ranking (SUCRA), which was used to rank the strategies and display the probability of each strategy being ranked first, showed the following: intermediate strict control (SUCRA 88%), liberal control (SUCRA 55.3%), very liberal control (SUCRA 40.3%), and strict control (SUCRA 16.5%). The cumulative probability of each strategy’s rank in reducing all-cause mortality, from best to worst, showed that the most likely ranking was intermediate strict control, liberal control, very liberal control, and strict control. Conclusions In ICU patients with diabetes, no significant statistical difference was observed among the four glucose control strategies in reducing all-cause 90-day mortality. The SUCRA rankings are hypothesis-generating and require further validation. Therefore, the current evidence is insufficient to definitively conclude that any one strategy is superior to the others in reducing mortality.